The Potential of Portable AR in Physics Education: A Study on Student Perceptions - Anselmo, Charlie T.; Saet, Artemio B.; Magleleong, Angelica P.; Cagayan, Apol Joy D.; Corpuz, Fely T. (Future Science / FSH-PH Publications, 2025)
Integrating portable augmented reality (AR) into physics education has the potential to enhance student engagement and learning outcomes. This study investigates students' perceptions of the appeal and effectiveness of the Traveling Virtual Lab (TVL), a solar-powered AR learning kit designed to improve physics education in the Philippines. A quantitative research design was employed, utilizing the